Leiomyoma of the bladder in a patient with von Recklinghausen's neurofibromatosis. - Däuth, T; Conradie, M; Chetty, R (2003)
Leiomyomas are an uncommon manifestation of neurofibromatosis type 1 (NF-1) and occur most often in the gastrointestinal tract. Here, they have a proclivity for the proximal small bowel and tend to be multiple. Urinary tract involvement by NF-1 is usually in the form of neurofibromas, and leiomyomas are exceptionally rare. This report describes a case of solitary leiomyoma occurring in a 49 year old woman with NF-1. The patient had symptoms related to a lower urinary tract infection and on examination was found to have a distended bladder. Imaging of the bladder showed a mass involving the posterior wall, neck, and trigone causing bilateral hydronephrosis. The mass was excised with part of the bladder. Microscopic examination revealed typical features of a leiomyoma and there was strong immunoreactivity for desmin and smooth muscle actin. Leiomyoma must be considered in the differential diagnosis of spindle cell neoplasms in patients with NF-1.